Anxiety in Pregnancy: A Literature Review - Fahma, Hilmia (Journal of Diverse Medical Research: Medicosphere, 2024)
Background. Pregnant women commonly faced anxiety. Not only affect their maternal health, but also contribute significantly foetus development. Identifying the contributing factors will drive to specific interventions given to the patients. Methods. We search from Pubmed and Google Scholar database using relevant keywords, such as "anxiety in pregnancy," "maternal anxiety," and "pregnancy stress." Discussion. Not only psychological factor, several others contribute significantly in anxiety of pregnancy. Both mother and foetus could suffer bad outcomes. Thus, interventions should comprehensively manage both mother health and foetus development. Conclusion. The anxiety in pregnancy had potential impact on the well-being of both the mother and the developing foetus. The critical importance of implementing comprehensive interventions to effectively address this significant issue.